International Strategies Of Danna Pharmaceutical Company In The Pharmaceutical Industry In Malaysia - Karbasi, Morteza (2011)
This study concerns about the growth and development of Danna pharmaceutical company to investigate Malaysian pharmaceutical market attractiveness to come up with suitable strategies in order to clear entry barriers.